Análise semântica de capas tipográficas de livros feministas: discussões sobre performatividade de gênero - Araujo Ferraz Oliveira, Gabriela; Lima, Samara (InfoDesign, 2021)
In this paper, we argue that books materialize cultural values and constitute a field of political and social dispute. We disregard the idea of typographic transparency and emphasize its semantic dimension, in order to understand the use of typography in book covers. Thus, we identified contrasts in common sense gender performativity and performativity present in feminist book covers. Finally, we realized a survey with women regarding semantic values assigned, firstly, to letterforms alone and, then, to letterforms in designed covers of five contemporary feminist books. Based on the survey results mainly made of semantic differential scales, we present the variety of confluences and divergences of interpretations of letterforms. Despite the diversity of results, none of the covers leans towards the hegemonic gender performativity staged in common sense.